Long-term adverse effects following COVID-19 vaccination - Jehad A. Aldali; Sultan Ayoub Meo (Medicine, 2026)
During the COVID-19 pandemic, vaccinations were highly beneficial to public health, preventing disease and reducing mortality. This study aimed to investigate long-term adverse clinical symptoms following COVID-19 vaccination with the Oxford AstraZeneca (ChAdOx1 nCoV-19, Oxford), Pfizer-BioNTech (BNT162b2), and Moderna (mRNA-1273) vaccines. In this cross-sectional study, the total number of participants was 429; among them, 243 (56.6%) were male, and 186 (43.4%) were female. An online Google Form was prepared in both Arabic and English and distributed to participants who received the Oxford AstraZeneca, Pfizer-BioNTech, and Moderna vaccines. The most common long-term adverse effects reported after COVID-19 vaccination were chronic fatigue, impaired cognitive function, and menstrual irregularity. The Moderna vaccine had a higher self-reported symptom rate among male participants (50–61.5%) than among female participants (33.3–28%). Chronic fatigue was more frequent among Oxford AstraZeneca recipients (34.7%) than among Moderna (22.2%) and Pfizer-BioNTech (27.7%) recipients. The second dose was associated with slightly higher rates of chronic fatigue among Oxford AstraZeneca recipients (38.9%) than among Moderna (25%) and Pfizer-BioNTech recipients (27.3%). For cognitive problems, the prevalence was similar across all brands (25%). Menstrual irregularity was slightly higher among females who received Pfizer-BioNTech (14.8%) than among Oxford AstraZeneca recipients (18.9%). The highest proportion of recipients who were infected after vaccination was among those who received the Oxford AstraZeneca vaccine (46.3%). In conclusion, the most commonly reported long-term adverse effects after COVID-19 vaccination were chronic fatigue, cognitive impairment, and menstrual irregularity. Further large-scale studies are required to provide more conclusive evidence.